2021
DOI: 10.1038/s41598-021-93944-9
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of early learning and movement sub-structure predictive of motor performance

Abstract: Time-to-fall off an accelerating rotating rod (rotarod) is widely utilized to evaluate rodent motor performance. We reasoned that this simple outcome could be refined with additional measures explicit in the task (however inconspicuously) to examine what we call movement sub-structure. Our goal was to characterize normal variation or motor impairment more robustly than by using time-to-fall. We also hypothesized that measures (or features) early in the sub-structure could anticipate the learning expected of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…In addition, sustained depletion of neutrophils until late phase increased infarct volume with the extent similar to CAMP −/− mice (Figure 2(f) to (g)). In terms of the neurological function after MCAO, we found that the modified Garcia score and time-to-fall off an accelerating rotating rod (rotarod test) 34 were both significantly decreased in the CAMP −/− mice compared to the WT mice 7 days after MCAO (Figure 2(h)). In the grid-walking test, the percentage of forelimb foot fault (right impaired forelimb foot fault/total amount of right forelimb step) were significantly higher in CAMP −/− mice compared to WT mice (Figure 2(h)) during 14 days after MCAO.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, sustained depletion of neutrophils until late phase increased infarct volume with the extent similar to CAMP −/− mice (Figure 2(f) to (g)). In terms of the neurological function after MCAO, we found that the modified Garcia score and time-to-fall off an accelerating rotating rod (rotarod test) 34 were both significantly decreased in the CAMP −/− mice compared to the WT mice 7 days after MCAO (Figure 2(h)). In the grid-walking test, the percentage of forelimb foot fault (right impaired forelimb foot fault/total amount of right forelimb step) were significantly higher in CAMP −/− mice compared to WT mice (Figure 2(h)) during 14 days after MCAO.…”
Section: Resultsmentioning
confidence: 96%
“…8a, left panel). The rotarod test has been well-established to evaluate motor coordination and balance by assessing the time of falling from a programmed rotating rod 52, 53 . After the single-session tFUS with a PRF of 40 Hz at S1HL or thalamus and multi-session tFUS stimulation with the PRF of 40 Hz at S1HL or insula for 14 days, we did not find any significant difference in the averaged latency to fall compared with pre-stimulation baseline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rate of change of speed: Difference in the instantaneous speed between two successive frames divided by the inter-frame duration. Speed Smoothness/Spectral Arc Length: Smoothness of speed of a limb using MATLAB's 'fft' function (Jakkamsetti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While measuring these relations for the first two drugs (acetazolamide and baclofen), we observed differential effects on various measures of gait, indicating that individual body part movements are not uniformly amenable to modulation. Thus, to facilitate and expand this analysis, we drew upon a machine learning assisted method that we previously developed for rotarod motor evaluation (Jakkamsetti et al, 2021) using deep learning neural networks. This allowed for the identification of 49 locomotor parameters that differentiated G1D from control, which were differentially sensitive to treatment with saline as control or glucose as therapy.…”
Section: Introductionmentioning
confidence: 99%